Optimizing ground beef lean sources to maximize display color life - C. Raines; Melvin C. Hunt; John A. Unruh (Kansas Agricultural Experiment Station Research Reports, 2008)
It is widely accepted that meat color is the most important influencer of consumers' meat purchasing decisions. Understanding how ground cow meat discolors is, and will continue to be, very important as a large influx of cull dairy cows in the U.S. meat supply is predicted. Optimal management and more timely marketing of cows should result in increased revenue for the beef industry. However, many valuable by-products from cows have been labeled as specified risk materials accompanied by a lost value. Thus, there is an unprecedented need to add value to cow meat. Research characterizing cow muscles and how to optimally use them for ground beef production could increase the value of cull cows and result in improved management and use of meat from cull cows. Our objectives were to evaluate the display color life of ground beef from different muscle combinations that vary in pre-established color stability values and determine if using beef or dairy cow meat affects color dynamics and stability of ground beef.
Keywords: Cattlemen' s Day; 2008; Kansas Agricultural Experiment Station contribution; no. 08-212-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 995; Beef; Cattle; Meat color